"Nothing will come of nothing": an interview with Sir Richard Eyre - Eyre, Richard (Acta neophilologica, 2001)
The article features an interview with Sir Richard Eyre, a long-time Director of the Royal National Theatre in London and the director of the production of William Shakespeare's tragedy King Lear in the very same theatre in 1997, which also saw a successful film version. Sir Richard openly spoke about his dilemmas as a director in the process of staging the play, finding the right cast, about rehearsals and the first night performance, as well as about some key scenes interpreted by him somewhat differently, although he essentially firmly relied on the text and the moral traditional staging of this famous Shakespeare's tragedy.
Keywords: angleška dramatika; Eyre, Richard; gledališče; intervjuji; režiserji; Shakespeare, William, 1564-1616; theater; uprizoritve